Experimental investigation on combustion and emission characteristics for heavy fuel and used motor oils blends in a free-flames burner. (1st January 2022) - Gómez, Jaime; Neumann, Thomas; Guerrero, Fabián; Toledo, Mario
Highlights: Heavy fuel and used motor (UMO) oils blends were used in a free-flames burner. Fuel blends were preheated, and air injection regulated for minimum CO emissions. Temperatures and chemical products were measured and analyzed. Flames radiation heat transfer for blends were higher than for pure heavy fuel oil. Combustion efficiencies increased from 48.8% for UMO25 to 63.5% for UMO100. Abstract: The main objective of this experimental investigation is to evaluate the feasibility of heavy fuel (HFO) and used motor (UMO) oils blends combustion in a free-flames burner installed in an isothermal oven. Temperature and chemical products of the combustion process are reported for mass percentages blends from 25% to 100% UMO (UMO25, UMO50, UMO75, and UMO100). For these tests, a burner with preheated oil blends and a primary and secondary air injection system are considered. Firstly, pure heavy fuel oil (HFO100) combustion is tested on its thermal effect as a baseline, recording emission factors for gaseous and solid emissions. Then, fuel blends are tested using secondary air injection regulated for minimal CO emissions. Overall results show that: i) flames radiation heat transfer for fuel blends are higher than for HFO100, ii) combustion efficiencies increase in the range of 48.8% to 63.5% for UMO25 and UMO100, respectively, and iii) exergy balance with a preheated air combustion shows the highest value for UMO100. Finally, this study suggests that used motor oils as fuel have a potential application in free-flames combustion process.